Exploring unintentional drifts in finger force production and muscle activity: A study of finger independence - Tilley, Paul (My University, 2024)
Human beings cannot move or produce force with their fingers independently from each other. Finger independence is constrained by the central nervous system which coordinates force production via multi-finger synergies, among additional mechanical and peripheral neural factors. Finger interdependencies represented in the central nervous system rely on integrating tactile, proprioceptive, and visual feedback on task performance. The primary purpose of this thesis was to explore drifts in finger interdependencies in the absence of visual feedback. Twenty right-handed participants (10 females and 10 males, aged 18-29 years) performed a series of isometric, single finger flexion and extension exertions with digits II-V. The right arms of the participants were braced in a mid-prone position, with their right wrist at 0° flexion and digits II-V secured to uniaxial force transducers. The activity of flexor digitorum superficialis (FDS) 2-5 and extensor digitorum communis (EDC) 2-5 were recorded via surface electromyography. Participants performed 30 second static, single finger flexion and extension exertions at 15% and 30% of their maximum voluntary contraction (MVC) with digits 2-5. A single repetition of each exertion was performed in two conditions: (1) with continuous visual force feedback, and (2) with visual feedback removed following 10 s. When feedback was given for the whole trial, the uninstructed fingers drifted towards greater involuntary force production (~4% MVC between the four fingers) while FDS and EDC activity generally increased over time. Removing visual feedback on the instructed finger induced consistent downward force drifts in its force production at 15% and 30% MVC flexion and 30% MVC extension, along with decreased extrinsic finger muscle activity. In the flexion conditions, removing feedback also eliminated the upward uninstructed finger force drifts.
Keywords: finger independence; neuromuscular control; electromyography; muscle synergies; spatial referent control; force drifts; sensorimotor control